Compreendendo a reação ‘step-wise’ de conversão de metano a metanol usando zeólitas trocadas ionicamente com cobre - Mizuno, Stefanie Caroline Mayumi (2020)
Methane (CH4) is a stable molecule abundantly found on our planet with reserves even greater than crude oil. Due to its high availability and environmental impacts caused by its emission into the atmosphere, the development of processes for its conversion into high value-added products is highly desired. Direct conversion of CH4 to methanol is advantageous as this process converts CH4 at low temperatures (<300 ° C) through the step-wise methane to methanol direct conversion (MMet). Intense scientific studies have been conducted on this reaction and all of them converged to the use of metal ionexchanged zeolites, especially copper. Although CH4 is easily activated on these materials, controlling methane total oxidation to COx is still a challenge and a limiting for methanol yield. In addition, only a fraction of Cu species actually participates in the reaction, which means that methanol yield is also limited to this factor. Since different Cu structures can be formed in zeolites by copper exchanged method, such as [Cu3 (μ-O)3]2+, [Cu2 (μ-O) 2]2+, [Cu2 (μ-O)]2+, and CuO, there are still fundamental questions to be answered for a better understanding of this reaction, such as the effect of zeolite structure on the formation of Cu species and how to maximize its participation in the reaction. We herein carried out a careful study of different copper-exchanged zeolite materials varying several synthesis/reaction parameters and related the activity to the structure of the Cu species. Our results suggested that high Cu content and low Si/Al ratio were unfavorable and the counter ion affects the performance of mazzite zeolite on MMet reaction. With this study, we hope to contribute with important aspects that might help in a future process scale-up.